Fragmentation of rangelands: implications for humans, animals, and landscapes - Hobbs, N.T.; Galvin, K.A.; Stokes, C.J.; Lackett, J.M.; Ash, Andrew J.; Boone, Randall B.; Reid, Robin S.; Thornton, Philip K. (Elsevier, 2008)
Fragmentation of the ecosystems of the earth into spatially isolated units has emerged as a primary component of global change. Often, fragmentation results from actions that are intended to enhance human livelihoods and well-being; however, there are often costs to ecosystems and human economies that are not considered. We describe the three general categories of processes causing fragmentation of rangelands worldwide: dissection, decoupling, and compression. We show that access to heterogeneity of landscapes is an important attribute of grazing ecosystems worldwide, and that fragmentation of these systems, even when it proceeds in the absence of habitat loss, can limit options of people and animals, options that are particularly important in temporally heterogeneous environments. We discuss the consequences of fragmentation for people, livestock, wildlife, and landscapes and describe potential adaptations that can mitigate its harmful outcomes. We close by reviewing policy options that promote re-aggregation of landscapes and adaptation to fragmentation.